Planning a Fun Learning Model at SD Nusantara Lubuk Pakam - Nanda, Vira Dwi; Nasution, Abdul Gani Jamora; Khairizka, Wirda Indri (Yayasan Pendidikan Islam Akmalia, 2023)
The aim of this research is how to apply learning concepts to create a fun learning model. The method used in this research is qualitative-descriptive, this approach focuses on the researcher's understanding, thoughts and perceptions. The results of the researchers' perceptions of various materials regarding fun interest-based learning models are that students have different interests in certain subject matter at school. This cannot be separated from a fun learning model, so that students have an interest in continuing to study the material at the next level of education